A review on degradation of perfluorinated compounds based on ultraviolet advanced oxidation. (15th December 2021) - Wang, Xuelin; Chen, Zhongyun; Wang, Yonglei; Sun, Wenjun
Abstract: Perfluorinated compounds (PFCs), as emerging persistent pollutants, can exist for a long time in the environment due to their high stability. PFCs have been detected in drinking water, wastewater, and the human body. Studies have shown that PFCs pose a threat to human health and the ecological environment, which is expected to be listed in new drinking water regulations. Traditional processes, including coagulation, biological filtration, chlorination, ozonolysis, and ultraviolet light have ineffective removal efficiency on PFCs; however, advanced oxidation processes (AOP) based on ultraviolet (UV) light have good application prospects for the removal of PFCs. This study provides an overview of the removal of PFCs by UV-based AOPs; systematically introduces the research status of various UV-based AOPs from the perspectives of degradation pathways, degradation efficiency, influencing factors, formation of by-products; and comprehensively compares these different UV-based AOPs. Finally, the limitations of existing research and future research needs are discussed. This review aims to provide an overview for a better understanding of the degradation status and prospects of UV-based AOPs for the degradation of PFCs. Graphical abstract: Image 1 Highlights: Present UV-based AOP for degradation of PFOA and PFOS are discussed and reviewed. Operational factors influencing the removal efficiency are discussed and summarized. Degradation pathways and by-product formation of PFCs are evaluated and outlined. Advantages and disadvantages of different advanced oxidation processes are discussed. Knowledge gaps and research needs of PFC degradation are identified.